Proceedings of the 12th International Conference on Generative Programming: Concepts &Amp; Experiences 2013
DOI: 10.1145/2517208.2517209
|View full text |Cite
|
Sign up to set email alerts
|

Family-based performance measurement

Abstract: Most contemporary programs are customizable. They provide many features that give rise to millions of program variants. Determining which feature selection yields an optimal performance is challenging, because of the exponential number of variants. Predicting the performance of a variant based on previous measurements proved successful, but induces a trade-off between the measurement effort and prediction accuracy. We propose the alternative approach of family-based performance measurement, to reduce the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In theory, any combination of the configuration options may cause a distinct interaction pattern [43]. Fortunately, researchers have found that relevant interactions form a hierarchical relationship [42,43,45]. That is, higher-order interactions usually build on lower-order interactions.…”
Section: Hierarchical Interactionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In theory, any combination of the configuration options may cause a distinct interaction pattern [43]. Fortunately, researchers have found that relevant interactions form a hierarchical relationship [42,43,45]. That is, higher-order interactions usually build on lower-order interactions.…”
Section: Hierarchical Interactionsmentioning
confidence: 99%
“…Accordingly, HINNPerf mainly increases O (π‘š 2 𝑛𝑑) complexity compared to DeepPerf. However, based on the previous works [42,43,45] revealing that there are at most five-way interactions in configurable systems, we restrict π‘š ≀ 5 in our model. Therefore, the increase in model complexity caused by the parameter π‘š could be regarded as constant (i.e., O (π‘š 2 𝑛𝑑) β‰ˆ O (𝑀𝑛𝑑) where 𝑀 is a constant).…”
Section: Complexity Analysismentioning
confidence: 99%
See 3 more Smart Citations